What Else Can Surface Water Buffer Systems Do?—Exploring Multiple Ecosystem Services - Lei Wu; Rafael R. Muñoz-Carpena; Yuncong Li (EDIS, 2016)
As society confronts the consequences of global warming, deteriorating water quality, and impoverished biodiversity, there is a growing urgency to develop and expand water buffers' multifunctional ecosystem services. However, limited information is available on other potential co-benefits associated with the use of buffers, particularly VFSs. This 5-page fact sheet provides information on buffers' multiple ecosystem benefits, such as niche products production, carbon sequestration, and flood risk mitigation, as well as recommendations on future research needs necessary to enhance multiple ecosystem services and benefits of buffers. Written by Lei Wu, Rafael Muñoz-Carpena, and Yuncong Li, and published by the UF Department of Soil and Water Science, November 2015.